Fungal Innate Immunity Induced by Bacterial Microbe-Associated Molecular Patterns (MAMPs). Issue 6 (1st June 2016) - Ipcho, Simon; Sundelin, Thomas; Erbs, Gitte; Kistler, H Corby; Newman, Mari-Anne; Olsson, Stefan
Abstract: Plants and animals detect bacterial presence through Microbe-Associated Molecular Patterns (MAMPs) which induce an innate immune response. The field of fungal–bacterial interaction at the molecular level is still in its infancy and little is known about MAMPs and their detection by fungi. Exposing Fusarium graminearum to bacterial MAMPs led to increased fungal membrane hyperpolarization, a putative defense response, and a range of transcriptional responses. The fungus reacted with a different transcript profile to each of the three tested MAMPs, although a core set of genes related to energy generation, transport, amino acid production, secondary metabolism, and especially iron uptake were detected for all three. Half of the genes related to iron uptake were predicted MirA type transporters that potentially take up bacterial siderophores. These quick responses can be viewed as a preparation for further interactions with beneficial or pathogenic bacteria, and constitute a fungal innate immune response with similarities to those of plants and animals.